2014
DOI: 10.1177/1541344614551637
|View full text |Cite
|
Sign up to set email alerts
|

The Shark in the Vitrine

Abstract: The Scholars of Studying Teaching Collaborative engaged a dozen faculty members from 12 specializations and 4 colleges at a large public university in a 2-year teaching and research project with the goal of learning about and enacting a self-study of professional practice. Participants were selected from various disciplines to provoke alternative perspectives in whole group and critical friend teams. While we each conducted a self-study, we also designed and enacted a meta-study to assess our professional deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…As my educational values evolve in response to, and in relationship with, my lived experience and significant people in my life, I will be changing and learning. Samaras et al (2014) suggested that self-study forces you to confront your inadequacies and in so doing, you become more mindful of incongruities in your practice. As Samaras et al (2014, 368) commented, self-study is not linear and orderly but is characterised by "messiness, uncertainty and complexity" and for me this is what makes self-study so appealing.…”
Section: Resultsmentioning
confidence: 99%
“…As my educational values evolve in response to, and in relationship with, my lived experience and significant people in my life, I will be changing and learning. Samaras et al (2014) suggested that self-study forces you to confront your inadequacies and in so doing, you become more mindful of incongruities in your practice. As Samaras et al (2014, 368) commented, self-study is not linear and orderly but is characterised by "messiness, uncertainty and complexity" and for me this is what makes self-study so appealing.…”
Section: Resultsmentioning
confidence: 99%
“…White (2012) posited that youth suicide is "an unstable, historically contingent, and unruly problem [which] cannot be solved, nor contained through an exclusive reliance on predetermined, universal or standardized interventions" (p. 42). As such, learning experiences in child and youth care higher education that parallel the complexities encountered in practice and safe learning spaces are needed for students to question, take risks, share beliefs, express vulnerabilities, and accept others' feedback and perspectives (Samaras et al, 2014). Moments of fear and anxiety can be viewed as opportunities for learning that can lead to personal transformation (Walinga & Harris, 2016).…”
Section: Discussionmentioning
confidence: 99%